Three hundred patients treated with ultrapulsed 980 nm diode laser for skin disorders - Uwe Wollina (Wolters Kluwer Medknow Publications, 2016)
The use of lasers in skin diseases is quite common. In contrast to other laser types, medical literature about 980 nm ultrapulsed diode laser is sparse in dermatology. Herein, we report the use of ultrapulsed diode 980 nm laser in 300 patients with vascular lesions, cysts and pseudocysts, infectious disease, and malignant tumors. This laser is a versatile tool with excellent safety and efficacy in the hands of the experienced user.